Radiation influence on characteristics of GaP light emitting diodes - Borzakovskyj, A.; Gontaruk, O.; Kochkin, V.; Litovchenko, P.; Opilat, V.; Petrenko, I.; Tartachnyk, V. (Functional Materials, 2009)
The capacitance properties of GaP green and red LEDs have been studied. It was found the character of a doping impurity distribution in the depleted region and the junction depth dependence on bias voltage and impurity concentration in the low-doped part of the p-n junction have been established. The dependences of those quantities on the irradiation dose have been obtained (for E = 1 MeV electrons). In the case of alpha-particle bombardment (10²-10³ cm⁻¹), anomalous high carrier removal rate is explained by formation of disordered regions in irradiated samples. Наведено результати дослідження ємнісних характеристик зелених та червоних фосфідо-галієвих діодів. Визначено характер розподілу легуючих домішок у межах збідненої області, залежність ширини переходу від прикладеної напруги та концентрації домішки у слаболегованій частині p-n-переходу. Одержано залежність цих величин від дози опромінення (для електронів з Е = 1 МеВ). Аномально велике значення швидкості видалення носіїв при бомбардуванні а-частинками (10²-10³ cm⁻¹) пояснюється формуванням в опромінених зразках областей розупорядкування. Представлены результаты исследования емкостных характеристик фосфидо-галлиевых диодов зеленого и красного свечения. Выяснен характер распределения легирующих примесей в пределах обедненной области, зависимость ширины перехода от приложенного напряжения и концентрации примеси в слабо легированной части p-n-перехода. Определена зависимость этих величин от дозы облучения (для электронов с Е = 1 МэВ). Аномально большое значение скорости удаления носителей при бомбардировании а-частицами (10²-10³ cm⁻¹) объясняется образованием в облученных образцах областей разупорядочения.